ASSESSMENT OF HEAVY METAL CONTAMINATION IN WATER, SOIL AND VEGETABLES IN TWO URBAN STREAMS IN MACHAKOS MUNICIPALITY, KENYA. - TOMNO, MWENDE ROSE (MksU Press, 2022)
Presence of heavy metals in our environment is of great concern since the heavy metals bio-accumulate in food chains posing harmful health effects to humans who are consumers of food grown in such environments. This study sought to determine the concentration of selected heavy metals (Cd, Pb, Cr, Zn and Cu) in urban stream water, soil and vegetables (spinach and kale) in Machakos municipality. Water and soil samples were collected along the rivers under study. Vegetables (spinach and kale) grown along the rivers, as well as vegetables sold in the market sites in the municipality were also collected for analysis. All the collected samples were analyzed for heavy metal concentrations using the inductively coupled plasma mass spectrometer (ICP-MS). Before heavy metal analysis, the vegetable and soil samples were oven dried, ground and digested using a tri acid mixture (HNO3, HClO4 and HCl). The water samples were also digested in a tri acid mixture prior to heavy metal analysis. Physico-chemical parameters for the river water (temperature, pH, total dissolved solids (TDS) and electrical conductivity (EC)) were measured on-site using standard portable meters. The data was analyzed using the Minitab Statistical software, version 19. One -way Analysis of variance (ANOVA) was used to test for the significant difference (p≤0.05) of heavy metal concentrations in vegetables, soil, and water among the different sampling sites. Heavy metal concentrations were compared with acceptable standards by the World Health Organization (WHO) for irrigation water, agricultural soil and vegetables for human consumption. Carboxymethyl starch was synthesized and its ability to remove heavy metals from water through chelation determined. The mean levels of the Physicochemical parameters ranged from 7.5 – 8.45 pH, 21.58 – 23.05 ºC temperature, 577.5 – 865.83 mg/L total dissolved solids (TDS) and 864.83 – 1778.5 µs/cm electrical conductivity (EC). Mean values of pH were observed to be significantly different (p = 0.000) among the sampling sites. Temperature, pH and TDS were within the WHO recommended limit for surface water while EC values exceeded the World Health Organization (WHO) set limit. The mean concentrations (mg/L) for heavy metals in water were found to be; Cd (0.0005 – 0.0011), Cu (0.0034 – 0.0055), Pb (0.0012 – 0.007), Zn (0.0232 – 0.1351) and Cr (0.0036 – 0.0292), while mean values (mg/kg) in soil were; Cd (0.0058 – 0.0534), Cu (10.39 – 27.5), Pb (4.23 – 8.35), Zn (20.1 – 28.80) and Cr (8.17 – 10.03). Mean concentration values (mg/kg) for the heavy metals in vegetables were; Cd (0.004 – 0.243), Cu (0.909 – 14.5), Zn (9.05 – 26.7), Pb (0.098 – 0.0.867) and Cr (0.112 – 14.0). The levels of heavy metals in water and soil were found to be within the WHO acceptable standards. The mean concentration of Pb, Zn and Cr in vegetables from some of the sampling sites exceeded WHO acceptable levels. Pearson correlation matrix showed positive correlations between heavy metals concentrations in soil, water and vegetables. Carboxymethyl starch was found to chelate heavy metals to a greater percentage; 92.31% Cd, 66.90% Pb, 66.19% Zn, 66.18% Cu and 14.37% Cr, thus a potential material for remediation of heavy metals in water. Presence of heavy metals (Zn, Pb, and Cr) in spinach and kales signifies a health hazard from consumption of these vegetables. This study thus recommends proper treatment and disposal of effluent based on best practices and continuous monitoring of heavy metals in urban stream water, soil and vegetables as it is critical towards safe guarding public health.